2014
DOI: 10.1007/s00334-014-0500-0
|View full text |Cite
|
Sign up to set email alerts
|

Palynological and sedimentological evidence from the Trans-Ural steppe (Russia) and its palaeoecological implications for the sudden emergence of Bronze Age sedentarism

Abstract: At the turn of the second to the third millennium BC, fortified and systematically organized settlements along with a developed metallurgy emerged in the TransUral steppe. In order to reconstruct the related vegetation and climatic changes in the area and to detect effects of human impact during the respective Bronze-Age SintashtaPetrovka and Srubnaya-Alakul cultures (2100-1650 cal BC), palynological and sedimentological investigations accompanying archaeological excavations were carried out. Statistical analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 24 publications
1
27
0
Order By: Relevance
“…There are sporadic fir pollen records in tundra (Andreev et al 2005), foresttundra (Panova et al 2010) and in northern taiga close to the Urals (Kultti 2004) but no Abies pollen in more western sites (Henricksen et al 2008). In the southern Urals, there are sporadic records of Abies pollen in the forest-steppe during the Holocene (Lapteva & Korona 2012) but none in the steppe (Stobbe et al 2015). Regular but rare presence of Abies in the northern and southern pollen records may be explained by long-distance transport.…”
Section: Formation Of the Pre-uralian Hemiboreal Forests In The Holocenementioning
confidence: 93%
See 1 more Smart Citation
“…There are sporadic fir pollen records in tundra (Andreev et al 2005), foresttundra (Panova et al 2010) and in northern taiga close to the Urals (Kultti 2004) but no Abies pollen in more western sites (Henricksen et al 2008). In the southern Urals, there are sporadic records of Abies pollen in the forest-steppe during the Holocene (Lapteva & Korona 2012) but none in the steppe (Stobbe et al 2015). Regular but rare presence of Abies in the northern and southern pollen records may be explained by long-distance transport.…”
Section: Formation Of the Pre-uralian Hemiboreal Forests In The Holocenementioning
confidence: 93%
“…Cremer et al 2004;Kultti 2004;Andreev et al 2005;Henriksen et al 2008;Panova et al 2010;Svendsen et al 2014) and southern Ural mountains (e.g. Nemkova 1992;Lapteva & Korona 2012;Stobbe et al 2015). Studies in the middle Urals have been carried out mainly on the eastern slope (Blagoveshchenskiy 1940(Blagoveshchenskiy , 1943Sukachev & Poplavskaya 1946;Gorchakovskiy 1953;Maslennikova et al 2016;Panova & Antipina 2016), while the vegetation history of the western pre-Ural region is still very poorly studied.…”
mentioning
confidence: 99%
“…Other researchers argue for humidity and forest expansion as an attraction for settlement (Gayduchenko, ). Recent palynological and sedimentological analyzes at the Kamennyi Ambar settlement found that during the MBA this microenvironment was humid rather than dry and similar to today's conditions with no evidence for an expansion of the steppes and deforestation; pollen statistics revealed increased diversity of plant species, indicative of higher precipitation rather than drought (Stobbe, ; Stobbe et al, ; Stobbe, Gumnior, Rühl, & Schneider, ). The community could efficiently support itself and herds with the available pastures within 4 km of the settlement without overgrazing, and with the well‐network, herds could be maintained during winter months (Stobbe et al, ).…”
Section: Introductionmentioning
confidence: 94%
“…The assumption for the development for this new settlement pattern was traditionally viewed as a shift from pastoralism to a dedicated agro‐pastoral economy, or at least an economy more reliant on agriculture (Zdanovich & Zdanovich, ). However, archeological and paleoenvironmental data has, to date, produced no evidence for production and/or use of domesticated cereals at these sites, but rather a reliance on domestic and wild animal species, wild plants, and fish consumption (Rühl, Herbig, & Stobbe, ; Stobbe, ; Stobbe, Gumnior, Röpke, & Schneider, ; Ventresca Miller, Hanks, Judd, Epimakhov, & Razhev, ; Ventresca Miller et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, quantitative vegetation composition is modelled using pollen productivity estimates (e.g. Sugita et al, 2010;Trondman et al, 2015). Our pollen dataset was recently used to reconstruct plant cover quantitatively using the REVEALS model to describe the compositional changes in space and time, which is more reliable than using pollen percentages directly (Cao et al, 2019b).…”
Section: Potential Use Of the Siberian Fossil Pollen Datasetmentioning
confidence: 99%